Desain Analisis Sistem Informasi Laboratorium Rekam Medis Elektronik - Canggih Ajika Pamungkas; Zahra Anggra Aztiza; Ana Aprilia Anna Fingandari; Tina Rindiarum Dwinimastuti; Mutiara Nur Hanifah (Jurnal Sains dan Kesehatan, 2020)
This study aims to create an electronic medical record information design system where an electronic medical record system is a system that provides complete information on patient data and medical records during the maintenance and storage of all patient data. The Archive Management System at the Indonusa Surakarta Polytechnic Medical Records Laboratory is not yet computerized. Patient data entry still uses paper, while the recording and storage of medical records is done manually. This study aims to make applications related to electronic medical record information systems at the Indonusa Surakarta Polytechnic Laboratory. In this descriptive study the researcher used a qualitative approach, what will be done to the person in charge of the medical record laboratory. Based on the study results by conducting questionnaires and observations, data relevant to outpatient outpatient recordings is needed, for example medical information record numbers, patient data info, and disease data info, in designing an electronic medical record information system.